Diary entry by Patricia Whiting, November, 1986 - Whiting, Patricia, 1940-2010:::Creator::::::::::::
Diary entry by Patricia Whiting discussing personal growth and learning since the loss of her biological father eight months earlier. Included is a letter dated April 3, 1986 and written to Whiting's sister, mother, uncles, and aunt sharing Whiting's experience at the wake of her father.